Comparison of techno-functional and sensory properties of sponge cakes made with egg powder and different quality of powdered blood products for substituting egg allergen and developing functional food - Csurka, Tamás; Varga-Tóth, Adrienn; Kühn, Dorottya; Hitka, Géza; Badak-Kerti, Katalin; Alpár, Boglárka; Surányi, József; Friedrich, László Ferenc; Pásztor-Huszár, Klára (Frontiers in Nutrition, 2022)
Animal blood is a valuable resource, which is usually not utilized in a value-added way by the industry like other animal by-products, eventhough it has plenty benefit in terms of sustainability and human health especially against iron deficiency anemia. Animal blood is perfectly suitable for providing special functions, which are necessary for functional foods, and improve techno-functional properties based on the literature. In this paper powdered animal blood products (whole blood powder, blood plasma powder and hemoglobin powder) were substituted for egg powder in sponge cake. Techno-functional and sensory properties (texture by texture profile analysis and three-point breaking test, water activity, dry matter content, color) were instrumentally measured then a sensory evaluation was carried out by unskilled panelists. Quality characteristics (texture, color, dry matter content) were daily measured from the day of baking four times because fresh baked cakes are usually consumed in three days. Based on the results, powdered blood products are suitable for substituting for egg powder in sponge cakes and develop functional foods. The results show that powdered blood products can be used as a substitute for egg powder in sponge cakes and as a functional food. Blood powders can increase the hardness, chewiness and breaking force of cakes, giving them the ability to be stuffed with more fillings and molded into special shapes without compromising sensory characteristics, even increasing the intensity of the cocoa flavor, which results in a richer, darker color without deceiving consumers.